Branding Media Digital oleh Jamaah Mushola Sabilil Mustaqim dalam Pengembangan Pasar Yosomulyo Pelangi (Payungi) - Suhono Suhono; Dharma Setyawan; Haikal Haikal; Wiwied Pratiwi (Bulletin of Community Engagement, 2023)
The goal of this assistance was to create a more structured roadmap for the digital media movement through mentoring and assistance to increase skills in the management of traditional snack promotions and the use of digital media technology such as Instagram, fanpage, graphic design, and websites to impact financial markets' income or profitability for the community at Payungi (Pasar Yosomulyo Payungi). The method used ABCD (Asset Based Community) to maximize the potential assets, which includes individual assets, communities, infrastructure, community, et al. As a result of this assistance, the economy of the residents around Payungi was assisted and gave impact on new jobs, and good relationships among stake holders. The community could obtain information from credible sources, the audience receives interesting material. The strengthening of this assistance had an impact on this traditional creative market, both in terms of the turnover of traders and the creativity of business entrepreneurs. Hence, they can engage economic development, economic resilience and sustainability of the various programs that have conducted together. Keywords: Digital Branding Media, Pasar Yosomulyo Pelangi, Traditional Market Development